Effects of fertilisation on radionuclide uptake by maize from an acidic soil in northwestern Croatia - Zgorelec, Željka; Šoštarić, Marko; Babić, Dinko; Šestak, Ivana; Mesić, Milan; Perčin, Aleksandra; Petrinec, Branko (Soil & tillage research, 2021)
•NPK fertilisation suppressed the uptake of several radionuclides by maize.•No suppression for radionuclides which are or can mimic biogenic elements.•No suppression for radionuclides which accumulated on stem from air.•Low radionuclide concentrations in grain.•Fertilisation did not change the radiological properties of the soil. The goal of this study is to shed more light on the influence of fertilisation on radionuclide transfer from soil to crops, which is a significant ecological issue in present-day agriculture due to the intensive use of soil amendments. Research on this subject has not been extensive, hence there are still numerous open questions that require an interdisciplinary approach involving agroecology and radioecology. Maize was chosen for our investigation because it has been used, in considerable quantities and worldwide, as both food and feed, which makes it part of numerous food chains with humans as final consumers. The agricultural part of the experiment was carried out on an acidic soil in northwestern Croatia, and it was based on seven treatments with different levels of NPK fertilisation. Radionuclide activity concentrations in sampled soil, stem, and grain were measured by means of high-resolution γ-ray spectrometry. We found that the radiological properties of the soil were not affected by the addition of the fertiliser. Soil-to-stem uptake for radionuclides of the whole 232Th decay chain was first suppressed by mild fertilisation, and then, at higher fertiliser concentrations, it stayed low and became independent of fertilisation level. The same effect was observed for the 238U decay chain before gaseous 222Rn. We present arguments in favour of the cause of the observed suppression being radionuclide complexation with constituents of the fertiliser. However, the concentration of 210Pb in stem did not depend on fertilisation, which was most probably a consequence of the decay of airborne 222Rn and the deposition of its progenies onto stem. Radionuclide translocation from stem to grain did not depend on fertilisation either, and it was appreciable only for 40K and 137Cs. In grain, radionuclide concentrations were lower than in stem. Overall, in our case, fertilisation had positive effects, reducing the presence of radionuclides in the maize while having no detectable impact on the radiological properties of the soil. This finding may have implications for future work, especially regarding concerns about the impact of soil amendments on food production.